Crohn’s Disease Is Associated with Decreased CYP3A4 and P‑Glycoprotein Protein Expression - Wilson, Aze; Urquhart, Bradley L; Ponich, Terry; Chande, Nilesh; Gregor, James C; Beaton, Melanie; Kim, Richard B (Molecular pharmaceutics, 2019)
Cytochrome P450 (CYP) 3A4 and P-glycoprotein (P-gp) have broad substrate overlap and are involved in the metabolism and transport of nearly 50% of currently prescribed medications. In the intestine, CYP3A4 and P-gp are coexpressed in the enterocytes at the intestinal villous tip and act in a coordinated manner to limit drug and xenobiotic oral bioavailability prior to further metabolism and disposition in the liver. Crohn’s disease (CD), a form of inflammatory bowel disease, introduces a transmural intestinal insult that disrupts the intestinal barrier function; it therefore has the potential to affect intestinal drug metabolism and transport. We hypothesized that individuals with CD have reduced intestinal expression of CYP3A4 and P-gp. We obtained intestinal biopsy samples from individuals with and without CD and quantified the expression of CYP3A4 and P-gp. When we carried out Western analysis for protein expression, we observed a significant reduction in ileal (45% decrease) and colonic (78% decrease) CYP3A4 protein expression in subjects with CD compared with those without. Similarly, an 85% reduction in colonic P-gp protein expression was seen in the CD patients. Our data highlight important and novel findings pertaining to CD-associated changes to the intestinal expression of CYP3A4 and P-gp that are of relevance to better predict substrate drug dosing for patients with CD.